AI Conceptualisation And Nostalgic Marketing: Toward A Future Research Agenda On Meaning-Making And Consumer Engagement - Muh. Yushar Mustafa (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
: Artificial Intelligence (AI) has become a transformative force in contemporary marketing, enabling firms to personalize communication, automate decision-making, and generate consumer-oriented content at unprecedented levels. Despite these advancements, existing research predominantly treats AI as an implementation tool focused on prediction, recommendation, and content generation, while insufficient attention has been devoted to understanding how AI conceptualises and represents meaning. This limitation becomes particularly significant in nostalgic marketing, where consumer responses are shaped by memory, identity, authenticity, and emotional attachment. This study aims to develop a future research agenda that integrates AI conceptualisation approaches with nostalgic marketing mechanisms. Using an integrative conceptual analysis methodology, the study synthesizes literature from artificial intelligence, consumer behavior, nostalgia theory, identity theory, and marketing management to construct a comprehensive conceptual framework. The proposed framework positions AI conceptualisation as a meaning-making mechanism that influences consumer interpretation, authenticity perception, identity continuity, nostalgia intensity, and subsequent behavioral outcomes. Four conceptualisation strategies are identified, including embedding-based, knowledge-based, narrative-controlled, and hybrid representations, each expected to produce different effects on nostalgic consumer experiences. The framework further highlights authenticity and identity continuity as critical mediating mechanisms linking AI-generated content to emotional and behavioral responses. The study contributes to the literature by extending AI marketing research beyond predictive functionality and introducing conceptualisation as a critical explanatory construct. It also advances nostalgic marketing theory by incorporating AI-mediated meaning construction processes. Finally, the study provides a structured agenda for future empirical research and emphasizes the importance of transparency, authenticity, and ethical governance in AI-driven nostalgic marketing practices.